Immunity at Cauliflower Hydathodes Controls Systemic Infection by Xanthomonas campestris pv campestris. Issue 2 (9th February 2017) - Cerutti, Aude; Jauneau, Alain; Auriac, Marie-Christine; Lauber, Emmanuelle; Martinez, Yves; Chiarenza, Serge; Leonhardt, Nathalie; Berthomé, Richard; Noël, Laurent D.
Abstract : Brassicaceae hydathode anatomy affects infection by the adapted vascular pathogen Xanthomonas campestris pv campestris. Abstract: Hydathodes are water pores found on leaves of a wide range of vascular plants and are the sites of guttation. We report here on the detailed anatomy of cauliflower ( Brassica oleracea ) and Arabidopsis ( Arabidopsis thaliana ) hydathodes. Hydathode surface presents pores resembling stomata giving access to large cavities. Beneath, the epithem is composed of a lacunar and highly vascularized parenchyma offering a direct connection between leaf surface and xylem vessels. Arabidopsis hydathode pores were responsive to ABA and light similar to stomata. The flg22 flagellin peptide, a well-characterized elicitor of plant basal immunity, did not induce closure of hydathode pores in contrast to stomata. Because hydathodes are natural infection routes for several pathogens, we investigated hydathode infection by the adapted vascular phytopathogenic bacterium Xanthomonas campestris pv campestris ( Xcc ), the causal agent of black rot disease of Brassicaceae. Microscopic observations of hydathodes six days postinoculation indicated a digestion of the epithem cells and a high bacterial multiplication. Postinvasive immunity was shown to limit pathogen growth in the epithem and is actively suppressed by the type III secretion system and its effector proteins. Altogether, these results give a detailed anatomic description of Brassicaceae hydathodes and highlight the efficient use of this tissue as an initial niche for subsequent vascular systemic dissemination of Xcc in distant plant tissues.